Endoproteolytic Activity of the Proteasome - Liu, Chang-Wei (2002)
The proteasome plays a central role in the degradation of regulatory and misfolded proteins. Current models suggest that substrates access the internal catalytic sites by processively threading their termini through the gated substrate channel. Here, we found that latent (closed) and activated (open) proteasomes degraded two natively disordered substrates at internal peptide bonds even when they lacked accessible termini, suggesting that these substrates themselves promoted gating of the proteasome. This endoproteolysis provides a molecular mechanism for regulated release of transcription factors from inactive precursors as well as a means of accessing internal folding defects of misfolded multidomain proteins.